On approximation of thermodynamic driving force in deeply undercooled melts - Pillai, Suresh K.S.; Málek, Jiří (University of Pardubice, 2014)
The difference in Gibbs free energy between liquid and solid phases, usually expressed by authors as )G, appears in several theoretical formulations on nucleation and crystal growth. Approximations for )G are used extensively to gain an insight into the solidification phenomenon when thermophysical parameters are not known. In this work, the most commonly used models are applied to four bulk metallic glasses at temperatures starting from that of glass transition. An arithmetic mean of Thomson–Spaepen and Hoffman’s approximations yield significant improvements over new models incorporating nonlinear relationships involving undercoolings.